2023
DOI: 10.1007/s43069-023-00217-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Super-Efficiency of Working Capital Management Using Data Envelopment Analysis: Does COVID-19 Matter?

Abstract: This study evaluates the working capital management (WCM) super-efficiency in UAE firms and determines how the COVID-19 crisis may affect WCM super-efficiency from a statistical perspective. Data envelopment analysis (DEA), difference tests, and Tobit regression techniques are used. Integration of DEA with Tobit regression is required to recognize the potential statistical consequence of COVID-19 on the super-efficiency of WCM. The results show that WCM super-efficiency is moderate and requires decision-makers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…These results are compatible with Habib and Mourad (2023) findings, which reveal significant differences in U.S. firms' performance before and during the COVID-19 pandemic. In contrast, the results are incompatible with (Habib and Kayani, 2023;Habib and Mourad, 2022), as Habib and Kayani (2023) revealed no significant difference in UAE firms' performance before and during COVID-19, and Habib and Mourad (2022) revealed no significant difference in Gulf firms' performance before and during COVID-19.…”
Section: Differences Analysismentioning
confidence: 83%
See 2 more Smart Citations
“…These results are compatible with Habib and Mourad (2023) findings, which reveal significant differences in U.S. firms' performance before and during the COVID-19 pandemic. In contrast, the results are incompatible with (Habib and Kayani, 2023;Habib and Mourad, 2022), as Habib and Kayani (2023) revealed no significant difference in UAE firms' performance before and during COVID-19, and Habib and Mourad (2022) revealed no significant difference in Gulf firms' performance before and during COVID-19.…”
Section: Differences Analysismentioning
confidence: 83%
“…The Mann-Whitney U test is a statistical test that falls under the category of nonparametric tests. It is commonly employed to compare the means of two groups derived from a shared population (Habib and Dalwai, 2023;Habib and Kayani, 2023;Habib and Mourad, 2023a). This study uses the Mann-Whitney U test to check the null hypothesis that Romanian firms' performance distribution is the same before and during the COVID-19 crisis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamshari et al [ 80 ] argued that COVID-19 leads to the decline in WC performance, and a conservative WCM method is appropriate for most companies during the COVID-19 period. However, Habib and Kayani [ 81 ] concluded that COVID-19 does not significantly affects the efficiency of WCM. A Romanian study showed that NWC increases in 2020 compared to 2019 and it positively impacts corporate performance [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering this philosophy, business strategy is aligned with the theory of the firm, as the firm is seen as a cluster of complementary attributes, including the concentration of decision rights over productive assets, regulation of managerial hierarchies, employment contracts, and the use of incentives and implicit agreements to regulate transactions [ 12 ]. From this perspective, a firm can efficiently allocate resources to enhance its performance and achieve competitive advantages [ [13] , [14] , [15] ]. In addition, there are numerous other conceptualizations of the nature of the firm, some based on notions of firms as specialized collections of heterogeneous resources [ [16] , [17] , [18] ], some based on behavioral theory [ 19 , 20 ], while others emphasize the nature of firms as knowledge-based and learning entities [ [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%